A comparative finite element simulation of locking compression plate materials for tibial fracture treatment. Issue 10 (7th September 2021) - Beirami, Sami; Nikkhoo, Mohammad; Hassani, Kamran; Karimi, Alireza
Abstract: The locking compression plate (LCP) system has several advantages in fracture fixation combining angular stability with the use of locking screws with traditional fixation techniques. However, the system is complex and requiring careful attention to biomechanical principles and good surgical technique. Due to the set of complicate stresses and strains in the LCP system after implantation, the material, which is being used here, is deemed important. However, so far the materials have been limited to the stainless steel (SS) or titanium (Ti). This study was therefore aimed at investigate the biomechanical performance of the internal tibial locked plates at different material properties, including SS, Ti, carbon/polyether ether ketone (PEEK) composite, in treating medial tibial fracture using patient-specific finite element (FE) model of the human tibia. The carbon/PEEK composite materials were used at three different fiber plies configurations. Simulated loading was applied at 60:40 ratios on the medial:lateral aspect. The model was fixed distally in all degrees of freedom. The results revealed the highest stress (307.10 MPa) and the lowest strain (0.14%) at Ti LCP system. The carbon/PEEK LCP system at configuration I and III showed low stress (∼60 MPa) and high strain (0.70%), which are suitable points for designing of an internal LCP system. On the other hand, the highest value of stress in callus region was 4.78 MPa (Carbon PEEK/Configuration I) and the strain variations of callus region were between 1.46% and 3.82% among all materials. These results implied the advantage of carbon/PEEK composite materials in LCP system as they can tolerate higher strains at lower stresses.